ARCH-GARCH Analysis: An Approach to Determine The Price Volatility of Red Chili - Etty Puji Lestari; Sucihatiningsih Dian Wisika Prajanti; Wandah Wibawanto; Fauzul Adzim (AGRARIS: Journal of Agribusiness and Rural Development Research, 2022)
Red chili is an agricultural commodity with high price volatility. Several previous studies stated that volatility was caused by weather effect on red chili production and shocks on public consumption. However, the other research stated that volatility was caused by the government’s import of red chili. This research aimed to analyze the price volatility of red chili in Semarang Regency on January 2019 to February 2020. The ARCH-GARCH method was applied in this study. This research showed that the price volatility of red chili occurred at the beginning, middle, and end of the year due to climate change, changes in public consumption patterns on religious holidays, and oversupply. However, the prevalence of Indonesia’s imports of red chili did not affect the price volatility. The government is suggested to implement a mapping policy and planting patterns to ensure the supply of red chili.